A note on strictly cyclic Shifts on ℓp - Gerd H. Fricke (International Journal of Mathematics and Mathematical Sciences)
In this paper the author shows that a well known sufficient condition for strict cycliclty of a weighted shift on ℓp is not a necessary condition for any p with 1<p<∞.